Peningkatan Kemampuan Pemecahan Masalah Matematika Melalui Strategi Realistic Mathematics Education Berbasis Group Investigation Pada Siswa Kelas VIII SMP Muhammadiyah 7 Surakarta Tahun 2015/2016 - Khasanah, Nestiyani Uswatun, Drs.Nining Setyaningsih, M.si (2016)
The purpose of this research is to increase of mathematical problem solving ability by applying Realistic Mathematics Education based Group Investigation strategy in students of class VIII SMP Muhammadiyah 7 Surakarta. This type of research is classroom action research conducted in two cycles. This research was conducted in collaboration between researcher and teacher of mathematics. Subjects were students and teachers of math class VIII B. Data collection techniques used were observation, testing, documentation, field notes, and interviews. Data were analyzed using flow method that consists of data reduction, data presentation, and data verification. The results of this study showed an increased of mathematical problem solving ability. An increased of mathematical problem solving ability can be seen from the indicators: 1) the ability to understand the problem before action of 35%, after the act of 85%, 2) the ability to design plan for settlement before the action of 25%, after the act of 75%, 3) ability to implement the settlement plan before action 20%, after 70% action, 4) the ability to look back a step before the completion of action 15%, after 65% action. This study concluded that the implementation of the Realistic Mathematics Education based Group Investigation stretegy to improve of mathematical problem solving ability in class VIII B of SMP Muhammadiyah 7 Surakarta. Keyword: group investigation, mathematical problem solving ability, realistic mathematics education